If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(15x + -1) = 13x Reorder the terms: 5 + -1(-1 + 15x) = 13x 5 + (-1 * -1 + 15x * -1) = 13x 5 + (1 + -15x) = 13x Combine like terms: 5 + 1 = 6 6 + -15x = 13x Solving 6 + -15x = 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 6 + -15x + -13x = 13x + -13x Combine like terms: -15x + -13x = -28x 6 + -28x = 13x + -13x Combine like terms: 13x + -13x = 0 6 + -28x = 0 Add '-6' to each side of the equation. 6 + -6 + -28x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -28x = 0 + -6 -28x = 0 + -6 Combine like terms: 0 + -6 = -6 -28x = -6 Divide each side by '-28'. x = 0.2142857143 Simplifying x = 0.2142857143
| -11-3x=44 | | 9x/4=5/7 | | 30000/7500 | | 20x+10(2x)+10x+1(5x)=750 | | y=5+x^2+2x | | -5-2n=-2(1+n)-3 | | v+4.74=7.4 | | 18/3=v/7 | | 8(x-7)=-24-8x | | 64-x^6= | | 6(v-1)-6=-7(-4v+1)-7v | | 5y+2=3y+22 | | -3(-4-2n)=19+6n | | y+2=23(x-9) | | Y=10c | | t=(x-1)(1-x) | | 8/3y=5/6x-2 | | 20log(x)=-12 | | -62=1-9w | | -39-2x=7x-6(1+7x) | | X^2+6x=59 | | 8v=2(4v+-2) | | -3x+50=2x+10 | | -12=-2(x+5) | | In(2x)=-2 | | 4-7x+6x=0 | | t=(x-7)(2+y) | | 9m=6(a+4) | | -19=2+4(h+7) | | 754/1000000 | | 3x(2x-3)=27 | | 17j-6=14j+7 |